Everestmab, a novel long-acting GLP-1/anti GLP-1R nanobody fusion protein, exerts potent anti-diabetic effects - Hongchao Pan; Yunnan Su; Yini Xie; Weiyong Wang; Wanli Qiu; Wei Chen; Wenying Lu; Zhao Lu; Weiwei Wang; Anquan Shang (Artificial Cells, Nanomedicine, and Biotechnology)
In the present study, a novel single domain antibody (sdAb) fusion protein, named everestmab, composing of a mutated GLP-1(A8G) fused to the tandem bispecific humanized GLP-1R-targeting and albumin-binding nanobodies was designed and characterized for the therapies for type 2 diabetes mellitus (T2DM). Surface plasmon resonance (SPR) measurements demonstrated everestmab associates with serum albumins of rat and monkey species with high affinity, and tends to be cross-reactive with rat and monkey species. In vitro GLP-1R binding and activation assays revealed that everestmab can specifically activate the GLP-1R, and the antagonist exendin-4 (9–39) did not inhibit the activation yet. In vivo multiple oral glucose tolerance tests (OGTTs) and hypoglycaemic efficacy tests proved that a single injection of everestmab reduced the blood glucose for at least 144 h in Goto-Kakizaki (GK) rats. The plasma half-lives of 4.1 and 7.8 days were observed after a single s.c. administration of everestmab in SD rats and cynomolgus monkeys, respectively. Chronic treatment of everestmab to GK and diet induced obese (DIO) rats achieved beneficial effects on weight reducing, HbA1c lowering, glucose tolerance, liver and pancreas islet function impairment. In summary, everestmab is a unique G-protein-coupled receptor-targeted nanobody fusion protein and exerts potential as a therapeutic treatment for T2DM.